Nonlinear Controller with Dynamic Compensation for 6-DOF Manipulator in Practice - Tran, Minh Phuc; Ha, Thanh Binh; Tong, Hai Ninh; Tran Duc, Thien (Journal of Technical Education Science, 2023)
This paper presents a nonlinear controller with dynamic compensation for six degrees of freedom (6-DOF) manipulator Denso VS-6556 in practice. The manipulator is a complex nonlinear system with some limitations when applying a linear controller to control it. The nonlinear controller combines proportional derivative, and dynamic compensation is established to deal with this problem. The PD control is a linear controller, and dynamic compensation can cancel the nonlinear parts in the system. Therefore, the tracking problem is expected to result in a good performance. The stability and resilience of the entire system are examined using a Lyapunov technique. The test bench is built to ensure the conditions for experimentation; it includes card PCI QUAD04s, NI PCI-6713, industrial computer 610H Advantage, and MATLAB/Simulink in practice. Finally, the suggested control is subjected to the 6-DOF manipulator Denso 6556 and compared with the PD control to verify the effectiveness of the controller.